ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI TERAPI RENDAM KAKI AIR HANGAT UNTUK MASALAH KECEMASAN PADA IBU HAMIL DENGAN PREEKLAMPSIA - Fenny Andriani (2022)
The maternal mortality rate in Indonesia based on the intercensus population survey (SUPAS) is 305 per 100,000 live births and this figure is still far from the Sustainable Development Goals (SDG's) target of 70 per 100,000 per live birth. One of the top 3 causes of maternal death is hypertension in pregnancy, including preeclampsia. Preeclampsia is one of the complications in pregnancy which is characterized by an increase blood pressure ≥140/90 mmHg, proteinuria and edema. Preeclampsia is a high risk pregnancy. Therefore, pregnant women with preeclampsia can experience feelings of anxiety compared to mothers with normal pregnancies. Untreated anxiety can have a negative impact for both mother and fetus. In addition, it can also increase blood pressure and can make preeclampsia worse. Therefore, need anxiety management by non-pharmacologically to reduce anxiety with warm water foot soak theraphy. The instrument used as a measure of anxiety is the Perinatal Anxiety Screening Scale (PASS). The results showed that after the application of warm water foot soak theraphy, the anxiety problems in pregnant women with preeclampsia could be partially resolved. This is evidenced by a decrease in anxiety scores after warm water foot soak therapy was applied.This therapy can be used as an alternative in reducing anxiety.